Appraisal of guidelines and variations in recommendations on drug therapy for invasive aspergillosis prevention and treatment - Wang, Jing; Sun, Ju; Yang, Da-Wei; Wang, Hai-Shan; Meng, Wei; Li, Hong-Yan (Frontiers in Pharmacology, 2025)
BackgroundIn recent years, many guidelines related to aspergillosis have been published worldwide. However, no studies have applied assessment tools to systematically evaluate the quality of these guidelines.ObjectivesThis study aimed to assess the quality of clinical practice guidelines and compared their recommendations related to drug therapy for the prevention and treatment of invasive aspergillosis.MethodsElectronic databases, guideline development organizations, and professional society websites were searched to identify clinical practice guidelines for invasive aspergillosis published between 1 January 2013, and 12 September 2023. The Appraisal of Guidelines Research and Evaluation (AGREE) II instrument was used to evaluate the quality of the guidelines. Recommendations for the drug prevention and treatment of invasive aspergillosis were extracted and descriptively analyzed.ResultsAmong the 18 included clinical practice guidelines, the median scores and interquartile range for each AGREE II domain were: scope and purpose, 76.39% (69.1%, 80.21%); stakeholder involvement, 59.72% (50.35%, 67.02%); rigor of development, 64.58% (44.4%, 72.27%); clarity and presentation, 81.25% (68.06%, 91.32%); applicability, 41.67% (36.46%, 47.92%); and editorial independence, 76.05% (50%, 87.5%). Voriconazole and isavuconazole are recommended as first-line therapy for invasive aspergillosis currently. Posaconazole remains the first choice for invasive aspergillosis prophylaxis in patients with hematological malignancies.ConclusionThe development processes and reporting of invasive aspergillosis -related clinical practice guidelines varied and their quality requires improvement. The guideline recommendations have changed since the approval of isavuconazole.